Social Informatics: Mapping and Visualizing an Emerging Domain - Hoeffner, Lori; Smiraglia, Richard P. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Social informatics is an emerging domain within the field of information studies that investigates the interrelationship between society and technology. The objective of this study is to identify whether social informatics’ published literature conforms to the assumptions believed about domain coherence. L’informatique sociale est un domaine émergent de la famille des sciences de l’information, qui s’intéresse aux relations entre la société et la technologie L’objectif de cette étude est de déterminer si la littérature publiée en informatique sociale se conforme aux attentes par rapport à un domaine organisé et cohérent.